Images of the Moon and the Sun in the Poetry of F.H. Thompson - M. V. Semenikhina (Дискурс, 2023)
Introduction. The article considers the analysis of metaphorical models describing the Moon and the Sun, two key mythologems in the works of F.H. Thompson, a religious English poet of XIX-XX centuries. The research relevance is connected with the growing interest in the representation of the individual author's worldview in a poetic text and with the fact that the work of F.H. Thompson in Russian philology remains poorly studied.Methodology and sources. The research is based on the conceptual metaphor theory byLakoff and Johnson. The empirical basis of the study was the poems by F.H. Thompson “A Corymbus for Autumn”, “Orient Ode”, “Ode to the Setting Sun”, “The Mistress of Vision”, “An Anthem of Earth”, “Sister Songs”, “From the Night of Forebeing”, “The Hound of Heaven”, “The Song of Hours”, “The Sere of the Leaf”, “The Dead Astronomer”, “Ad Amicam”, “Ad Castitatem”, “Love Declared”, “Of Nature: Laud and Plaint”, “Nocturn”, “Assumpta Maria”, “To a Poet Breaking Silence”, “Arab Love-Song”, “Victorian Ode”.Results and discussion. The analysis revealed that in F.H. Thompson's poetry the images of the Moon and the Sun are contrasted as “passive – active”, “weak – strong”, “chastity – passion”, “cold – heat”, “water – fire”, to a lesser extent “death – life”, “female – male” and “pagan – Christian”. The Sun is a source of life, beauty and poetic inspiration, and, in addition, the movement of the Sun across the sky during the day helps people to understand the story of Christ’s death and resurrection and its sense. The Moon, despite its coldness and passivity, also plays a necessary role in the universe (for example, controlling natural cycles and acting as an intermediary between the Sun and mankind).Conclusion. The images of the Moon and the Sun fit seamlessly into the general system of images of Thompson's poetry, in which the author seeks to create an image of a spiritualized Universe filled with the presence of God. The Sun is the central image of Thompson's poetry, an active character, often likened to Christ; the Moon is more passive and more strongly associated with paganism and death (which, however, does not make its image negative).